Angiotensin converting enzyme and endotoxin induced lung damage in the mouse. Issue 10 (October 1985) - Cookson, W O; Wiseman, M S; Shale, D J
Abstract : Acute pulmonary oedema can be induced by intraperitoneal injection of Escherichia coli endotoxin in the mouse. A fall in serum angiotensin converting enzyme activity is found in mice given endotoxin and in patients with septic adult respiratory distress syndrome, and has been proposed as an indicator of lung microvascular injury. Protein concentration and angiotensin converting enzyme activity in serum, lung, and bronchoalveolar lavage fluid were determined in male mice up to eight hours after injection of endotoxin. By six hours the serum protein concentration had increased and the bronchoalveolar lavage fluid protein concentration had fallen, suggesting fluid shift into the lung. Angiotensin converting enzyme activity fell in serum and lung but increased in bronchoalveolar lavage fluid. As these changes in enzyme activity were not paralleled by changes in protein concentration they are unlikely to be a result of fluid shift or protein leak, and may indicate an active role of the enzyme in the response to sepsis.